Five‐year risk of CIN3 after short‐term HPV‐DNA negativity in cytology‐negative women: a population‐based cohort study. (25th August 2019) - Del Mistro, A; Giorgi Rossi, P; Frayle, H; Pasquale, L; Campari, C; Ronco, G; Zorzi, M
Abstract : Objective: To assess the 5‐year risk of high‐grade lesions in women with a transient high‐risk HPV infection. Design: Population‐based cohort study. Setting: HPV primary testing within population‐based organised cervical cancer screening programmes. Population: Italian women enrolled in seven pilot projects and attending the second round. Methods: On the basis of the cytology triage performed on HPV‐positive women, immediate colposcopy or HPV repeat at 12 months was recommended. Data were collected at the subsequent round 3–4 years after HPV infection clearance. Main outcome measures: Rates of HPV infection, CIN2+ and CIN3+ detection at subsequent round after HPV clearance, and relative risks (RR) in comparison with HPV‐negative women (with 95% confidence interval). Results: Data on 1230 women (1027 aged 25–64 years and 203 aged 35–64 years) have been analysed. Overall compliance with repeat HPV testing was 84%. In comparison with HPV‐negative women, those with a transient HPV infection had higher proportions of HPV positivity (15% versus 3.7%) and of CIN2+ lesions (0.87% versus 0.23%) in round two; most of these (7/10) were CIN2; no cancers were detected, and CIN3 occurred in 3/1230 (0.24%). Conclusions: HPV‐based protocols for cervical cancer screening allow long intervals for HPV‐negative women; it is important to monitor the clinical outcome in the women with transient high‐risk HPV infection. CIN3 detection is similar to that observed in routine European cytology‐based screening programmes (CIN3+: 2.7‰); 5‐year intervals may provide reasonable protection but longer intervals are not recommended. Tweetable abstract: A screening interval of 5 years (but no longer) appears safe in women with transient HPV detection. Tweetable abstract: A screening interval of 5 years (but no longer) appears safe in women with transient HPV detection.